2012
DOI: 10.1038/npp.2012.158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genetic Variant in BICC1 on Functional and Structural Brain Changes in Depression

Abstract: Genes and early-life adversity (ELA) interactively increase the risk of developing major depressive disorder (MDD). A recent genomewide association study suggests that the minor T-allele of single-nucleotide polymorphisms in the bicaudal C homolog 1 gene (BICC1) has a protective role against MDD. The aims of the study were to investigate whether the minor T-allele of BICC1 is protective against hippocampal structural brain changes, whether it is associated with increased functional brain activity in the emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…However, in the CA1 region, there was no significant regulation of BICC1 mRNA in MDD subjects. In each of these areas, covariate analyses showed no significant effect of age, sex, PMI, or (Bermingham et al, 2012), where hippocampal size and dlPFC function were both affected by the BICC1 SNP.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, in the CA1 region, there was no significant regulation of BICC1 mRNA in MDD subjects. In each of these areas, covariate analyses showed no significant effect of age, sex, PMI, or (Bermingham et al, 2012), where hippocampal size and dlPFC function were both affected by the BICC1 SNP.…”
Section: Resultsmentioning
confidence: 91%
“…One recent genome-wide association study (GWAS) identified two SNPs in the bicaudal C homolog 1 (BICC1) gene showing suggestive significance for association in depressed patients compared to psychiatrically healthy controls (Lewis et al, 2010). In addition, a recent structural and functional imaging study corroborated this association with the finding that the minor T allele of the BICC1 SNP showed a protective role against MDD and the accompanying structural and functional changes in hippocampus and other limbic brain regions (Bermingham et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…Examples of the genes that have been investigated in this regard include genes involved in monoaminergic signalling such as the monoamine oxidase A (MAOA) (Gizatullin et al, 2006;Bellivier et al, 1998), tryptophan hydroxylase 1 (TPH1) (Gizatullin et al, 2006), and serotonin transporter (5-HTT) genes (Bellivier et al, 1998;Caspi et al, 2003;Frodl et al, 2010). Mediators of neuronal plasticity have been studied as well, such as the brain derived neurotrophic factor (BDNF) (Arlt et al, 2013;Lavebratt et al, 2010) and BicC family RNA binding protein 1 (BICC1) (Bermingham et al, 2012) genes. However, all genome-wide association analyses that have been performed have so far found inconclusive results regarding the association between SNPs in all these genes and MDD, suggesting that environmental factors may be crucial for developing the disease regardless of genetic vulnerability (Gyekis et al, 2013;Bosker et al, 2011;Clarke et al, 2010;Cohen-Woods et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported significant genotype‐diagnosis interaction effects on emotional regulation systems for FKBP5, CACNA1C, CRHR1, and BICCI genes. The remaining studies showed decreased activation of the striatum with a PCLO risk allele, decreased activation of right frontal middle gyrus in a 5‐HT2A T‐allele, or decreased connectivity of amygdala‐prefrontal circuitry with the MAOA H‐allele.…”
Section: Resultsmentioning
confidence: 91%
“…Hippocampal alterations were associated with genetic variants in ApoE ε4, NCAN, AGTR1, BICCI‐1, GSK3β, and TESC genes . The significant associations between morphological alterations in prefrontal regions were observed for variants in ApoE ε4, NET, and GSK3β genes .…”
Section: Resultsmentioning
confidence: 91%